Transcatheter valve-in-valve implantation in a degenerated very small Mitroflow prosthesis. (15th June 2018) - Lopez, Stéphane; Meyer, Pierre; Teboul, Jacques; Deharo, Pierre; Mihoubi, Alain; Elbeze, Jean Pierre; Lena, Diane; Camarasa, Philippe; Laborde, Jean Claude; Drogoul, Laurent
Abstract: OBJECTIVES: To assess the feasibility and results of 'valve-in-valve' implantation using the 23-mm CoreValve for the treatment of degenerated 19-mm and 21-mm Mitroflow bioprostheses. METHODS: We retrospectively analysed all consecutive patients who underwent transcatheter aortic valve implantation for 19-mm and 21-mm Mitroflow bioprostheses. The height of implantation with respect to the ring of the Mitroflow prosthesis was targeted at −6 mm for the first 3 cases. In the following cases, the target was higher to promote free supra-annular movement of the leaflets. RESULTS: The procedure was successful in 17 of 18 patients (94%). For implantations above the limit of −6 mm, the mean gradient was 10.4 ± 2.6 mmHg compared with 28.1 ± 11.6 mmHg for implantations below the limit of −6 mm ( P < 0.01). For patients with severe stenosis as main mechanism of failure of the bioprosthesis, the mean post-procedural gradient was 31.2 ± 11.8 mmHg compared with 12.7 ± 6 mmHg in the absence of severe stenosis ( P < 0.01). Patient–prosthesis mismatch (indexed effective orifice area ≤ 0.85 cm 2 /m 2 ) and severe mismatch (indexed effective orifice area ≤ 0.65 cm 2 /m 2 ) were present in 83% (15 of 18) and 27% (5 of 18) of patients, respectively. We did not notice any complications following the procedures. Six months after the procedure, functional status was improved in all patients. CONCLUSIONS: Our short series demonstrates the ability to perform transcatheter 'valve-in-valve' implantation in 19-mm and 21-mm Mitroflow prostheses with satisfactory results, but high post-procedural gradients and patient–prosthesis mismatch remain a relatively frequent problem mostly when severe stenosis is the main mechanism of failure. Implantation in a high position is critical to decrease the rate of high postimplantation gradients.